Stage 4 Lung Cancer with Brain and Pericardial Metastases Which Are First Considered as Pulmonary Tuberculosis Infection and Heart Failure - Haryati Haryati; Marsheilla Riska (Berkala Kedokteran, 2020)
Abstract: Lung cancer and pulmonary tuberculosis become a global problem in the world. The similarities of clinical symptoms and radiological appearances often complicates diagnosis especially in TB endemic countries. A 43-year-old man presented with shortness of breath for 6 months, accompanied by intermittent cough mixed with blood streaks. He had been taking anti-tuberculosis for 2 months, but there’s no improvement. On physical examination, ronchi were heard in the lower 2/3 of the right lung and heart sounds diminished. Motoric movement of the left hand was difficult to grasp hard. A contrast-enhanced CT scan of the head revealed hyperdense multiple nodules. Chest X-ray showed cardiomegaly with right lung consolidation and a primary malignant right lung mass accompanied by pericardial effusion at thoracic CT scan. Cytology and EGFR examination of pericardial effusion found adenocarcinoma metastasis with exon 18 and 21 mutations. Evaluation of clinical symptoms and radiological examination during tyrosine kinase inhibitor (TKI) therapy showed improvement. Lung cancer can resemble pulmonary tuberculosis in various manifestations. Adenocarcinoma with positive EGFR mutations is more commonly found in Asians. Cytology and EGFR examination of pericardial effusion became the basis of diagnosis in this case. He was given TKI therapy. Re-evaluation must be carried out in patients who do not improve with antibiotics or anti-tuberculosis. Patient reported a good response after consuming EGFR-TKI. Keywords: lung cancer, tuberculosis, tyrosine kinase inhibitors